Analisis Keaktifan Belajar IPAS dengan Model Problem Based Learning Berbantuan Quizwhizzer Pada Siswa Kelas V Sekolah Dasar - Fatimah, Siti; Prasetyowati, Dina; Sartika, Dwi (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to analyze the activeness of learning science and technology using the Problem Based Learning model assisted by quizwhizzer in class V elementary school students. This type of research is qualitative with a descriptive approach. The subjects of this research were class V teachers and class V elementary school students in one of the elementary schools in the city of Semarang. Data collection techniques used include observation, interviews and documentation. The results of the research show that the indicators of active learning have been met with the Problem Based Learning model assisted by quizwhizzer in class V of elementary schools, which has very good criteria. Indicator 1 level of achievement 85.18% very good criteria, indicator 2 level of achievement 70.37% good criteria, indicator 3 level of achievement 81.48% very good criteria, indicator 4 level of achievement 92.59% very good criteria, indicator 5 level of achievement 88.88% very good criteria, indicator 6 achievement level 77.77% very good criteria, indicator 7 achievement level 96.29% very good criteria, indicator 8 achievement level 70.37% good criteria.